1997
DOI: 10.1128/jb.179.10.3171-3180.1997
|View full text |Cite
|
Sign up to set email alerts
|

p-Cymene catabolic pathway in Pseudomonas putida F1: cloning and characterization of DNA encoding conversion of p-cymene to p-cumate

Abstract: Pseudomonas putida F1 utilizes p-cymene (p-isopropyltoluene) by an 11-step pathway through p-cumate (p-isopropylbenzoate) to isobutyrate, pyruvate, and acetyl coenzyme A. The cym operon, encoding the conversion of p-cymene to p-cumate, is located just upstream of the cmt operon, which encodes the further catabolism of p-cumate and is located, in turn, upstream of the tod (toluene catabolism) operon in P. putida F1. The sequences of an 11,236-bp DNA segment carrying the cym operon and a 915-bp DNA segment compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 87 publications
1
108
0
Order By: Relevance
“…It was concluded that P. putida CE2010 first degrades biphenyl to 6-phenyl-HOHD using the tod pathway enzymes, and degraded further by CmtE (Fig. 1), which is constitutively expressed by the less effective binding of the repressor CymR to the cmt operator region (Eaton, 1997) due to the changed nucleotide. No base difference was found in cymR in P. putida strains F1 and CE2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was concluded that P. putida CE2010 first degrades biphenyl to 6-phenyl-HOHD using the tod pathway enzymes, and degraded further by CmtE (Fig. 1), which is constitutively expressed by the less effective binding of the repressor CymR to the cmt operator region (Eaton, 1997) due to the changed nucleotide. No base difference was found in cymR in P. putida strains F1 and CE2010.…”
Section: Discussionmentioning
confidence: 99%
“…These operons encode enzymes that catalyse p-cymene to p-cumate, and p-cumate to TCA cycle intermediates, respectively ( Fig. 1) (Eaton, 1996(Eaton, , 1997. The cmt degradation pathway is similar to the tod pathway, except that the former incorporates one more reaction step of decarboxylation after ring cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This family of oxygenases is able to introduce one atom of oxygen into hydrophobic substrate using one atom of oxygen originating from molecular oxygen. The other oxygen atom is reduced to water using two electrons from NAD(P)H. The electrons are transferred from the NAD(P)H to the monooxygenase by either ferredoxin and ferredoxin reductase or cytochrome b5 in the case of fatty acid desaturases [156] rubredoxin and rubredoxin reductase in the case of alkane hydroxylases (AlkB) [157,158] or a ferredoxin-ferredoxin reductase fusion protein for xylene monooxygenases [22,[159][160][161]. Three, four or six membranespanning elements can be identified in all primary amino acid sequences of proteins belonging to this super-family, with varying numbers of amino acids between each transmembrane helix [162,163].…”
Section: The Membrane-bound Protein Non-heme Iron Oxygenasesmentioning
confidence: 99%